TRANSFORMASI RUMAH: PROSPEKNYA UNTUK MEMPERBAIKI KEADAAN RUMAH DI INDONESIA (SUATU STUDI PENDAHULUAN) - Putu Sueca, Ngakan (Jurnal Natah; Vol. 2, No. 1 Februari 2004, 2012)
The shortage of housing in urban areas of Indonesia has been an obvious reality for long period of time even worse since the economic turmoil in 1997. The question is how will we deal with the problems? What approach can we grasp so that we can improve housing condition effectively? This is a preliminary study of housing transformations that may provide major contribution for housing in the future. This paper is based on literature review of a wide range of case studies all over the world. The result shows that through transformations, owner-occupiers can gain a considerably more space not just to accommodate their domestic activities but also to generate income, reach a higher social status and improve housing conditions. Through intensive and extensive research, it has been found that housing transformations can considerably heighten housing conditions. Even without any supports or aids from the government, extension activities have continuously enlarged and enhanced housing condition. So, I suggest that transformations must be a suitable alternative for housing provision, probably not just in urban areas of Indonesia but also in rural areas. In the light of the international literature, it is likely that we could benefit from a favorable attitude towards housing transformations in Indonesia. Unfortunately, we rarely find research in this area especially in Indonesian context. So, it needs further studies as a basis for making appropriate solutions of housing problems in the specific conditions.
Keywords: housing transformation, lack of housing, housing provision mechanism